2016
DOI: 10.1001/jamaneurol.2016.0576
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral Microbleeds and Thrombolysis

Abstract: Using intravenous thrombolysis in a stroke patient with cerebral microbleeds represents one of the most challenging clinical decisions in acute stroke neurology. In this setting, the implications of coexisting ischemic and hemorrhagic cerebrovascular disease(mixed cerebrovascular disease) 1 must be confronted and urgently addressed. The clinical consequences of intervening or not intervening are profound.What exactly are the consequences? The greatest concern, of course, is the risk of thrombolysis-induced int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 14 publications
0
14
0
Order By: Relevance
“…Moreover, CMB increases with age for all locations in a general population (21), and age may be compounded by important vascular comorbidities for development of CMB (22, 23). Both CADASIL and hypertension have important effects on arteriolar function, with both processes targeting vascular smooth muscle cells (5). …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, CMB increases with age for all locations in a general population (21), and age may be compounded by important vascular comorbidities for development of CMB (22, 23). Both CADASIL and hypertension have important effects on arteriolar function, with both processes targeting vascular smooth muscle cells (5). …”
Section: Discussionmentioning
confidence: 99%
“…We recently proposed a “two site” model of CMB and ICH, in which the specific vascular sites for development of CMB and ICH are different (5). In both CADASIL and hypertension, (arteriolar) smooth muscle cells and blood–brain barrier are targeted; the former has been suggested as site for ICH and the latter a site for CMB (5). While the findings of the current study are consistent with this model, further mechanistic investigations are needed to confirm the observation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies have reported more extensive vascular calcification in both intracranial and extracranial arteries (internal carotid and coronary arteries) in patients with cerebral small vessel disease, including those with CMB [15][16][17]. Vascular calcification could disrupt the ability of brain arterioles to compensate for changes in systemic blood pressure, leading to a rise in the intraluminal pressure within the microvasculature and subsequent erythrocyte extravasation contributing to microhemorrhage formation [9,[18][19][20]. The potential mechanisms relating vascular calcification and CMBs are complex and further studies are needed to gain a better understanding.…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, we investigated stroke events and the progression of CMB in patients who were initially evaluated and managed in a stroke clinic. We attempted to identify biomarkers for progression of CMB, using a recently proposed conceptual framework in which CMB development is associated with arterial abnormalities related to dysfunctional regulation of cerebral blood flow [9]. We therefore analyzed clinical outcomes and intracranial calcification in patients with CMB.…”
Section: Introductionmentioning
confidence: 99%